Some New Aspects of Metric Fixed Point Theory - Khalil Javed; Fahim Uddin; Hüseyin Işık; Tareq M. Al-shami; Faizan Adeel; Muhammad Arshad (Advances in Mathematical Physics)
In this manuscript, we prove fixed point results in Rm-metric spaces endowed with an amorphous binary relation. Moreover, we give an example to highlight the utility of our main results. Finally, we apply our result to examine the existence and uniqueness of the solution for a Fredholm integral equation.